2014
DOI: 10.1186/1423-0127-21-60
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective and anti-inflammatory effects of PAL31 overexpression in glial cells

Abstract: BackgroundAcute spinal cord injury (SCI) leads to a series of reactive changes and causes severe neurological deficits. A pronounced inflammation contributes to secondary pathology after SCI. Astroglia respond to SCI by proliferating, migrating, and altering phenotype. The impact of reactive gliosis on the pathogenesis of SCI is not fully understood. Our previous study has identified an inflammatory modulating protein, proliferation related acidic leucine-rich protein (PAL31) which is upregulated in the microg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…LPS, also known as endotoxin, is often used to induce inflammation and apoptosis in the experiment and is the main component of the cell wall of Gram-negative bacteria. In this study, C6 glial cells were used as an in vitro model [ 28 ]. The results showed that LPS-stimulated C6 cells to produce an inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…LPS, also known as endotoxin, is often used to induce inflammation and apoptosis in the experiment and is the main component of the cell wall of Gram-negative bacteria. In this study, C6 glial cells were used as an in vitro model [ 28 ]. The results showed that LPS-stimulated C6 cells to produce an inflammatory response.…”
Section: Discussionmentioning
confidence: 99%